A Conceptual Exploration of Phonetic Transcription in Improving EFL Learners’ Pronunciation - Yudha Fergian Nugroho; Arif Suryo Priyatmojo (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Pronunciation continues to be a significant hurdle for numerous EFL learners, especially in situations where particular English phonemes do not exist in their native language. Although prior research has examined different techniques like mobile apps, phonetic exercises, and shadowing methods. Phonetic transcription is frequently overlooked as an organized tool for teaching pronunciation. This conceptual article suggests a gradual way to integrate phonetic transcription, specifically the International Phonetic Alphabet (IPA), into EFL classrooms to enhance long-term pronunciation improvement. The discussion is structured into four primary sections: the common pronunciation difficulties encountered by learners, the phonetic transcription, the importance of phonetic transcription for enhancing pronunciation, and the incorporation of this method into education. Based on theories and earlier studies, the findings indicate that phonetic transcription can enhance pronunciation skills among EFL learners. Additionally, once learners familiar with English phonemes, they can independently search for phonetic transcriptions in dictionaries or online resources.